2017
DOI: 10.1002/ptr.5984
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin mediated down‐regulation of αVβ3 integrin and up‐regulation of pyruvate dehydrogenase kinase 4 (PDK4) in Erlotinib resistant SW480 colon cancer cells

Abstract: Erlotinib is a potent, selective, and orally active inhibitor of the epidermal growth factor receptor, but the development of erlotinib resistance during chemotherapy can lead to treatment failure. To shed light on the erlotinib-resistant pathway, this study investigated the effect of combination therapy using curcumin- and erlotinib-loaded nanoparticles on the expression of α β integrin and pyruvate dehydrogenase kinase 4 (PDK4) in an erlotinib-resistant SW480 colon cancer cell line. An erlotinib-resistant SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The disruption of integrin function caused a significant reduction in the activation of Akt and thereby decreased the levels of the migration promoting factor ENPP2 (50). In addition, curcumin is shown to be down-regulate integrin αvβ3 that could benefit to the treatment of erlotinib resistant colon cancer cells (51).…”
Section: Potential Compounds Targeting Integrins For Anti-cancer Apprmentioning
confidence: 99%
“…The disruption of integrin function caused a significant reduction in the activation of Akt and thereby decreased the levels of the migration promoting factor ENPP2 (50). In addition, curcumin is shown to be down-regulate integrin αvβ3 that could benefit to the treatment of erlotinib resistant colon cancer cells (51).…”
Section: Potential Compounds Targeting Integrins For Anti-cancer Apprmentioning
confidence: 99%
“…Curcumin is one of the components of turmeric. It has been shown that synthetic dimethoxycurcumin is more potent to destroy cancer (a leading cause of every sixth death worldwide) cells than natural curcumin (derived from the plant) [54][55][56][57][58][59][60][61][62][63][64]. Ramírezagudelo et al [55] incorporated antibiotic doxycycline drugs (inhibitors of mitochondrial biogenesis, could restrict cancer stem cells in initial breast cancer stages) into electrospun hybrid poly-caprolactone/gelatin/hydroxyapatite soft nanofibrous mats and evaluated these drug delivery meshes as effective anti-tumor and antibacterial scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used for therapeutic purpose histologically due to the intrinsic anti‐inflammatory, antioxidant and antitumour properties . The extensive investigations and exploitations have characterized the wide‐spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth . The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The extensive investigations and exploitations have characterized the wide-spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth. [20][21][22][23][24][25] The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis. However, the potential antitumour effect of curcumin against ESCC has not been extensively explored despite the sporadic reports conducted in immortalized human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%